Therapeutic hypothermia potential in the critical patient treatment - Nogueira dos Anjos, Claudia; Cerqueira, Luciana Aparecida; Pinheiro Santiago, Gisele; de Moraes, Tania Mara (O Mundo da Saúde, 2008)
Therapeutic aims of hypothermia are known since the Eighteenth century and currently health professionals are emphasizing its use. It can be classified as light, moderate or deep. The work aims to show the potential of therapeutic hypothermia in the treatment of the critical patient. The work was elaborated from a systematic survey of books and scientific articles of SciELO, Lilacs and Medline databases in the period from 1984 to 2006. One uses this technique to provide neuroprotection in traumatic cerebral injuries, encephalic vascular accidents, intracranial hypertension, subaracnoid hemorrhage, among other neurological conditions, besides acute myocardium infarct and cardiorespiratory arrest. The main cooling techniques are cooled external/superficial, endovenous fluid infusion and extracorporeal/ central. Reheating techniques are passive and active, both external and internal. Time span and speed of both these techniques are vital to determine the effectiveness of hypothermia in the prevention and reduction of neurological injuries. It is a highly promising treatment, but its use is not much common in clinical practice, due mainly to the lack of hospital facilities and studies regarding its benefits and complications, and this makes necessary more studies about it, as well as improvement of professionals regarding its use.